Impact of Sex and Cardiovascular Risk Factors on Myocardial T1, Extracellular Volume Fraction, and T2 at 3 Tesla: Results From the Population-Based, Hamburg City Health Study. (20th September 2022) - Cavus, Ersin; Schneider, Jan N.; Bei der Kellen, Ramona; di Carluccio, Eleonora; Ziegler, Andreas; Tahir, Enver; Bohnen, Sebastian; Avanesov, Maxim; Radunski, Ulf K.; Chevalier, Celeste; Jahnke, Charlotte; Ojeda, Francisco; et al.
Abstract : Background: Reliable reference intervals are crucial for clinical application of myocardial T1 and T2 mapping cardiovascular magnetic resonance imaging. This study evaluated the impact of sex and cardiovascular risk factors on myocardial T1, extracellular volume fraction (ECV), and T2 at 3T in the population-based HCHS (Hamburg City Health Study). Methods: The final study sample consisted of 1576 consecutive HCHS participants between 46 and 78 years without prevalent heart disease, including 1020 (67.3%) participants with hypertension and 110 (7.5%) with diabetes. T1 and T2 mapping were performed on a 3T scanner using 5b(3b)3b modified Look-Locker inversion recovery and T2 prepared, fast-low-angle shot sequence, respectively. Stepwise regression analyses were performed to identify variables with an independent impact on T1, ECV, and T2. Reference intervals were defined as the interval between the 2.5% and 97.5% quantiles. Results: Sex was the major independent influencing factor of myocardial native T1, ECV, and T2. Female patients had significantly higher upper limits of reference intervals for native T1 (1112–1261 versus 1079–1241 ms), ECV (23%–33% versus 22%–32%), and T2 (36–46 versus 35–45 ms) compared with male patients (all P <0.001). Cardiovascular risk factors, such as diabetes and hypertension, did not systematically affect native T1. There was an independent association of T2 by hypertension and, to a lesser degree, by left ventricular mass, heart rate (all P <0.001), and body mass index ( P =0.001). Conclusions: Sex needs to be considered as the major, independent influencing factor for clinical application of myocardial T1, ECV, and T2 measurements. Consequently, sex-specific reference intervals should be used in clinical routine. Our findings suggest that there is no need for specific reference intervals for myocardial T1 and ECV measurements in individuals with cardiovascular risk factors. However, hypertension should be considered as an additional factor for clinical application of T2 measurements. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03934957.